Comparison of two methods used to prepare smears of mouse lung tissue for detection of Pneumocystis carinii. - Thomson, R B (1982)
The laboratory diagnosis of Pneumocystis carinii pneumonia in humans includes the identification of cysts in stained lung tissue impression smears. By using a mouse model, we compared the number of cysts in lung tissue impression smears with those contained in a concentrate of homogenized lung tissue. Eleven C3H/HEN mice developed P. carinii infection after corticosteroid injections, a low protein (8%) diet, and tetracycline administered in drinking water. Impression smears were prepared with freshly bisected lung tissue. Smears of concentrates were prepared with sediment from centrifuged lung tissue homogenates. All smears were made in duplicate, stained with toluidine blue O or methenamine silver, coded, randomized, and examined. The concentrate preparations contained more cysts per microscopic field than the impression preparations (P less than 0.01). Concentrates prepared by grinding with a mortar and pestle contained more cysts than concentrates prepared by blending with a Stomacher (P less than 0.05). Cysts were detected equally well with either the toluidine blue O or silver stain (not significant). Lung tissue concentrates were superior to lung tissue impressions for detecting P. carinii cysts in mice. Use of lung tissue concentrates should be considered for the diagnosis of human P. carinii infection.